The Syuro-Participative Leadership in Al-Qur’an-Based Pesantren in the Disruption Era - Muh. Mustakim; Ahmad Salim; Kana Safrina Rouzi; Ruwet Rusiyono; Desy Khusna Nurmaida (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This study discussed the renewal of leadership models in Al-Qur'an-based pesantren. Leadership in pesantren has a major influence on its development and existence. Ibn Abbas Islamic Boarding School is interesting to study because it is modern managed. This is a case study to examine in depth the developed leadership model. The data were collected through observation, documentation, and interview, and analyzed using the Miles Huberman triangulation model, so that the results were in the form of abstractions showing their novelty. Pesantren Ibnu Abbas Klaten is led by a director who acted as a manager as well as mufti and kyai. The director supervises three educational units; the pesantren, the santri, and the school unit, which each led by a chief. Even though a director (or Kyai) has full leadership rights, the